Temporal land-use change of a reclaimed land in greater Dhaka and its impact on natural water cycle - Huq, Md Habibul; Rahman, Md Mafizur; Hasan, G M Jahid (MIST International Journal of Science and Technology, 2024)
This study aims to explore the land-use induced impact on runoff and recharge of an impending urban growth on reclaimed land filled with sands in greater Dhaka to concede the low impact development through practicable methods. Having analyzed the temporal land-use change by Curve Number (CN), GIS-based Soil Conservation Service - Curve Number (SCS-CN) method has been used to evaluate the runoff of the study area. Initial land-use in 2010 with a higher CN 86 resulted in a lower CN 72 in 2020-2022 due to land-use change (pre-developed/existing condition) with permeable soil for urban development. However, the gradual land-use change resulted in more imperviousness and an increasing trend in CN. With ultimate CN 84, approximately 243% more runoff was predicted during complete urbanization in 2040 and beyond as opposed to CN 72 in 2020-2022. Due to the existing higher groundwater table of the area, the Water Table Fluctuation (WTF) method has been used to find the natural recharge potential. As higher CN results in more runoff and recharge loss, ultimate natural recharge potential with CN 84 declines to more than 50% of the pre-developed condition. Results from the methods suggested a comprehensive hydrological forecasting due to land-use change on reclaimed land with assorted options for natural water cycle balance. MIJST, Vol. 12, June 2024 : 35-49 DOI: https://doi.org/10.47981/j.mijst.12(01)2024.448(35-49)